Comparison of the Effectiveness of Counseling with Social Media, Animation and Short Films in Improving Perception and Motivation to Do Physical Activity in Adolescents - Razi, Pahrur; Junita, Junita; Marsofely, Reka Lagora; Marleni, Wisuda Andeka; Iksarudin, Iksarudin (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Physical activity is an essential component for health, low physical activity in Indonesia causes a high death rate, with 70% of all deaths among adults (including due to heart and lung disease). Therefore, efforts are needed to increase healthy lifestyles, especially physical activity, by providing health information through the media. The purpose of this study was to compare the effectiveness of counseling with social media, animation and short films as health promotion media to increase perceptions and motivation to do physical activity in adolescents. The design of this study is Quasi Experiment with a total sample of 180 people taken by total sampling. The data collection technique uses a physical activity questionnaire. Data analysis using the Anova test. The results of the analysis obtained that counseling with short films was more effective in increasing perceptions and motivation to carry out physical activities in adolescents at SMAN 3 Muaro Jambi indicated by a significance value at 0.000 (p <0.05) compared to social media and animation. There was a more significant increase in perception and motivation to do physical activity after counseling with short films compared to counseling using social media and animation for teenagers at SMAN 3 Muaro Jambi. Suggestions for further research are to examine the factors that influence perceptions and motivation for physical activity in adolescents.